Chromosome Analysis before Birth and its Value in Genetic Counselling. Issue 5779 (9th October 1971) - Ferguson-Smith, M. E.; Ferguson-Smith, M. A.; Nevin, N. C.; Stone, M.
Abstract : Chromosome analysis of amniotic cell cultures was achieved in 29 out of 30 consecutive patients who were referred for genetic counselling during pregnancy. Amniocentesis was performed without any apparent untoward maternal or fetal complication. The only pregnancy terminated was that of a carrier of X-linked granulomatous disease, in whom the amniotic cells showed that the fetus was male and also had Down's syndrome (trisomy G). Chromosome analysis in the remaining 28 patients showed normal karyotypes. The interval between amniocentesis and a definitive karyotype varied from 7 to 31 (average 18·4) days. The reliability of chromosome analysis from amniotic cell culture and of fetal sex determination by means of the sex chromatin and Y-fluorescence techniques was studied further in amniotic fluid from cases of therapeutic abortion and of rhesus incompatibility. The fetal sex was correctly determined in all cases. It is concluded that antenatal diagnosis of genetic disease by amniocentesis now permits a more practical approach to genetic counselling.